INTEGRATED HEALTH INFORMATION SYSTEM IN THE REPUBLIC OF SERBIA - Veličković, Jasmina; Lutovac, Mitar; Jokić, Mia (Annals of Nursing, 2024)
The Republic of Serbia's integrated health information system (IHIS) serves as a central electronic repository for storing and processing various medical and health-related data. It encompasses patient records, institutional information, details of health interventions and services, electronic prescriptions, appointment scheduling for specialist consultations, diagnostic procedures, and surgical operations. The implementation of this system promises several benefits, including improved access to patient information, expedited diagnostics, enhanced medication selection processes, heightened patient safety measures, more comprehensive health-statistical reporting, and accelerated dissemination of biomedical knowledge. This paper aims to explore the advantages of employing information technologies in healthcare delivery within health institutions, contrasting it with traditional methods of data collection, analysis, and interpretation, specifically focusing on primary healthcare institutions. Drawing upon current professional and societal perspectives, the paper discusses the conceptual framework and objectives of IHIS, emphasizing the significance of leveraging information technologies in healthcare.
Keywords: IHIS, healthcare, digitization, information security, information health system